Toward lateral heterostructures with two-dimensional MoX2H2 (X = As, Sb). Issue 39 (1st October 2020) - Tan, Ruishan; Lei, Yanzi; Li, Luyan; Shi, Shuhua
Abstract : Lateral heterostructures with 2D MoX2 H2 enable tunable bandgap engineering and type-II band alignment. Abstract : The development of two-dimensional (2D) lateral heterostructures (LHs) with the powerful tunability of electronic properties will be of great realistic significance for next-generation device applications. Herein, we report the novel 2D MoX2 and MoX2 H2 (X = As or Sb) monolayer materials with excellent stability. Using first-principles calculations, we demonstrated that 2D MoX2 layers possess the metallic characteristic while the full surface hydrogenation effect would play a role in stabilizing the 2D lattices and lead to band gap openings of 0.83 and 0.50 eV for the 2D MoAs2 H2 and MoSb2 H2, respectively. In addition, our results suggest that the 2D MoAs2 H2 and MoSb2 H2 can serve as the 'building blocks' to construct the seamless LHs exhibiting excellent thermal and dynamical stability. The obtained n L-MoAsSb LHs enable the fully tunable band gap engineering behavior with linear tendency as a function of the width of the in-plane components. The phase transition from direct to in-direct band gap was also confirmed in the LHs as the crucial value of n = 3. In view of the type-II band alignment and efficient carrier separation in n L-MoAsSb, the predicted MoX2 H2 and n L-MoAsSb LHs not only highlight the promising candidates for 2D pristine materials, but also paves the way for the realization of practical integrating device applications.